Macular choroidal small-vessel layer, Sattler’s layer and Haller’s layer thicknesses: the Beijing Eye Study - Zhao, Jing; Jonas, Jost B. (Scientific reports, 2018)
To study macular choroidal layer thickness, 3187 study participants from the population-based Beijing Eye Study underwent spectral-domain optical coherence tomography with enhanced depth imaging for thickness measurements of the macular small-vessel layer, including the choriocapillaris, medium-sized choroidal vessel layer (Sattler’s layer) and large choroidal vessel layer (Haller’s layer). In multivariate analysis, greater thickness of all three choroidal layers was associated (all P < 0.05) with higher prevalence of age-related macular degeneration (AMD) (except for geographic atrophy), while it was not significantly (all P > 0.05) associated with the prevalence of open-angle glaucoma or diabetic retinopathy. There was a tendency (0.07 > P > 0.02) toward thinner choroidal layers in chronic angle-closure glaucoma. The ratio of small-vessel layer thickness to total choroidal thickness increased (P < 0.001; multivariate analysis) with older age and longer axial length, while the ratios of Sattler’s layer and Haller’s layer thickness to total choroidal thickness decreased. A higher ratio of small-vessel layer thickness to total choroidal thickness was significantly associated with a lower prevalence of AMD (early type, intermediate type, late geographic type). Axial elongation-associated and aging-associated choroidal thinning affected Haller’s and Sattler’s layers more markedly than the small-vessel layer. Non-exudative and exudative AMD, except for geographic atrophy, was associated with slightly increased choroidal thickness.
Gesehen am 03.04.2020